Poverty and Wealth in Traditional African Societies: Considerations Regarding Wealth, Well-being and Nutrition in the Ganda and Nyoro Societies, c 1800 to 1875 (Nordic Journal of African Studies, 2000)
Poverty and Wealth in Traditional African Societies: Considerations Regarding Wealth, Well-Being, and Nutrition in the Ganda and Nyoro Societies, c 1800 to 1875